The fascinating effect of niobium as catalytic promoting agent. - Guerrero-Pérez, María Olga (Elsevier, 2019)
Niobium is a very important element in catalysis, active component of many catalytic systems. But it is not only a major component in many catalytic systems; in addition, it is usually used as a key promoter, because it has a rich complex chemistry and is able to react with many elements forming a wide range of compounds and oxide phases with complex structures. Thus, present contribution makes a brief review on the main industrial catalytic processes in with niobioum have been used as a promoting agent during the last decade. The uses of niobium as main component in the catalytic formulations have not been considered.
Keywords: Niobio; Catálisis; Niobium; Catalysis